ADVANCEMENTS OF THE BANK OF INDONESIA LIQUIDITY ASSISTANCE (BLBI) TASK FORCE: ACHIEVEMENTS AND CHALLENGES - Bayu Adinegoro; Effy Zalfiana Rusfian (Kanun Jurnal Ilmu Hukum, 2023)
Under the Indonesian Presidential Decree Number 6 of 2021, the government formed a task force to deal with the problem of the state claiming rights over the distribution of Bank Indonesia Liquidity Assistance (“BLBI”) funds received by obligors in 1998. During the Task Force's three-year operational period, collections have only reached about 27% of the outstanding target of IDR 110.45 trillion. This study evaluates the effectiveness of the collecting program's implementation under the applicable laws and regulations. The article indicates that the collection of BLBI receivables, as per the regulations outlined in GR 28/2022, has not been executed efficiently. This can be attributed to various factors, encompassing both the content and the context. The article proposes several viable alternatives, such as upgrading the legal framework for collecting BLBI receivables from being governed by GR to being embedded in law, and extending the BLBI Task Force's working period to achieve the best results for the welfare of the Indonesian people.